Submitting to God's will: Attitudes and beliefs of Moroccan Muslim women regarding mourning and remembrance. Issue 8 (14th September 2019) - Ahaddour, Chaïma; Van den Branden, Stef; Broeckaert, Bert
Abstract: This study aimed to elicit the attitudes and beliefs of middle-aged and elderly Moroccan Muslim women regarding mourning and remembrance, to identify whether differences are observable between middle-aged and elderly participants, to explore the role of religion and to document how the actual attitudes of our participants relate to normative Islamic literature. Interviews were conducted with middle-aged and elderly Moroccan women living in Belgium ( n  = 30) and with experts in the field ( n  = 15). This study reveals that the religious beliefs have a great impact on the views of Muslim women. We found striking similarities between our participants' views and normative Islamic literature.